Evaluasi Corporate Social Responsibility : Respon Kinerja Perusahaan (Studi Kasus Pada Pusat Perbelanjaan “X” Di Kota Madiun) - Ditta, Aliffianti Safiria Ayu; Sari, Erma Wulan; Dhamayanti, Yolanda (Universitas PGRI Madiun, 2024)
This research aims to evaluate the implementation of corporate social responsibility using the value for money model. Company performance is seen from three sectors, namely economic, social and environmental. This research uses a case study approach at a shopping center in Madiun City during the period 2020-2022 to see the differences that occurred before the Covid-19 pandemic occurred and during the pandemic. The result is a decreased allocation of CSR costs due to financial pressures and economic performance whose impact is most visible compared to social and environmental performance. The results of the value for money model evaluation show that the company absorbs almost 100% of the CSR budget and CSR effectiveness and efficiency has decreased due to the Covid-19 pandemic. The company's CSR program is in accordance with the GRI-4 and ISO 26000 indexes even though when preparing the CSR program, the company did not use these two indices as guidelines.